Assessment of student education quality in the field of study – state and municipal management by the experience of the Federal internet-examination for graduates of bachelor degree - V. Yu. Maslihina; E. D. Bogatyrev; T. G. Kolesnikova; O. V. Poryadina (Открытое образование (Москва))
Information base of research consists of informational and methodological support (model of pedagogical measuring materials and evaluation model, bank of tasks and the results of their implementation during the period 2014–2016) in the field of study 38.03.04 (081100.62) state and municipal management (undergraduate level). Content analysis, statistical methods and tests are used in this research.Directors of institutes and deans of faculties, heads of departments, academic staff and leading lecturers of universities, belonging to the Association of leading universities in Economics and Management, participated in the discussion of the pedagogical measuring materials as well as the lecturers, who are independent experts in the competitive commissions and the commissions on observance of requirements to office behaviour of state civil servants and settlement of interests’ conflict in state and municipal executive authorities. At the development stage it was organized the internal reviewing and mutual testing of tasks, independent review and expertize of the created pedagogical measuring materials were carried out by the specialists with an extensive experience in executive authorities.The article is dedicated to the experience of independent assessment of quality for graduates of bachelor degree in the field of study 38.03.04 state and municipal management, the normative study assessment is given. The exam programme, the structure of pedagogical measuring materials and test results of students are analyzed. Examples of tasks are given.The analysis of quantitative indicators of participation of Russian universities and students in the Federal internet-examination for the graduates of bachelor degree showed the exam demand and the public interest in information on its results, which can be used to make different managerial decisions with the purpose of improving the quality of higher education.